Adult neurogenesis augmentation attenuates anhedonia and HPA axis dysregulation in a mouse model of chronic stress and depression. (February 2021) - Eliwa, Hoda; Brizard, Bruno; Le Guisquet, Anne-Marie; Hen, René; Belzung, Catherine; Surget, Alexandre
Abstract: Major depressive disorder is a common debilitating mental health problem that represents one of the leading causes of disability. Up to date, the therapeutic targets and approaches are still limited. Adult hippocampal neurogenesis (AHN) has been proposed as a critical contributor to the pathophysiology and treatment of depression, altering the hippocampal control over stress response at network, neuroendocrine and behavioral levels. These findings together have suggested that manipulating AHN may be a promising therapeutic strategy for depression. To investigate this question, we assessed whether increasing adult neurogenesis would be sufficient to produce antidepressant-like effects at behavioral and neuroendocrine levels in a mouse model of depression; the unpredictable chronic mild stress (UCMS). For this purpose, we used a bi-transgenic mouse line (iBax) in which AHN increase was induced by deletion of the pro-apoptotic gene Bax from the neural progenitors following the tamoxifen-dependent action of CreERT2 recombinases. UCMS induced a syndrome that is reminiscent of depression-like states, including anhedonia (cookie test), physical changes (coat deterioration, reduced weight gain), anxiety-like behaviors (higher latency in the novelty-supressed feeding –NSF– test), passive stress-coping behaviors (immobility in the forced swim test –FST–) and a blunted hypothalamo-pituitary-adrenal (HPA) axis reactivity to acute stress in addition to AHN decrease. Tamoxifen injection reversed the AHN decrease as well as partly counteracted UCMS effects on the cookie test and HPA axis but not for the coat state, weight gain, NSF test and FST. Taken together, our results suggest that a strategy directing at increasing AHN may be able to alleviate some depression-related behavioral and neuroendocrine dimensions of UCMS, such as anhedonia and HPA axis reactivity deficits, but may be hardly sufficient to produce a complete recovery. Highlights: Chronic stress model induces depression-like behavioral and neuroendocrine symptoms. Neurogenesis augmentation in stressed mice alleviates anhedonia-like behaviors. Neurogenesis augmentation in stressed mice attenuates HPA axis dysregulation. Neurogenesis augmentation is not sufficient for a complete recovery.